The benefit of stool mycobacterial examination to diagnose pulmonary tuberculosis for adult and elderly patients. (August 2019) - Konno, Aya; Narumoto, Osamu; Matsui, Hirotoshi; Takeda, Keita; Hirano, Yuta; Shinfuku, Kyota; Tashimo, Hiroyuki; Kawashima, Masahiro; Yamane, Akira; Tamura, Atsuhisa; Nagai, Hideaki; Ohta, Ken; et al.
Abstract: Background: In patients with suspected pulmonary tuberculosis, who have difficulty in expectorating sputum, alternative specimens by invasive procedures, gastric aspirate or sputum suction, are not always available in the feeble elderly. Several studies report the benefit of stool test for pediatric or HIV infected patients, but few in adult patients. Objective: To evaluate the benefit of stool examination as non-invasive alternative test to detect Mycobacterium tuberculosis (MTB) infection. Methods: Stool specimens were examined for mycobacteria in 187 cases of microbiologically-diagnosed pulmonary tuberculosis between September 2013 and August 2017. We retrospectively reviewed the medical records to determine the positive detection rate of MTB with stool specimens and investigated factors related to MTB detection. Results: Among 187 patients included, positive rate of MTB in stool was 12.8% (24/187) by stool acid-fast bacilli smear, 68.1% (98/144) by TRC Rapid ®, and 40.6% (76/187) by culture. Multivariate logistic regression analysis revealed two contributing factors to MTB detection in stool; cavitation and male. The adjusted odds ratio with 95% confidence interval (CI) for cavitation was 2.9 (95%CI 1.48–5.69) and 2.1 (95%CI 1.08–3.93) for male. Conclusion: We recommend stool examination for those who are unable to give sputum and have risks for invasive procedures.